Unveiling the relationship between micro characteristics of particles and electrode performance in a 60 Ah high-energy-density Li-ion pouch cell. (1st January 2023) - Zhang, Haiyan; Pang, Jing; Wang, Rennian; Li, Xiang; Fang, Yanyan; Wang, Jiantao; Chen, Shengli; Lu, Shigang
Highlights: 1 The interactions within particles of different sizes are quantitatively analyzed. 2 The interparticle lithium diffusion and the intraparticle lithium diffusion are competitive. 3 The rest period during the CCCV protocol can be reduced for a higher cycle efficiency. 4 An appropriate kinetic matching between cathode and anode will reduce the lithium plating risk. Abstract: In order to get a super comprehensive performance, electrodes in high energy density batteries always consist of particles with different features. Thus, a deep insight into the interaction between particles can help to further improve the electrode performance. In this paper, an extended pseudo-2-dimension (P2D) model based on a 60 Ah high-energy-density (HED) Li-ion pouch cell (≥280 Wh kg −1 ) with Si-based anode/Ni-rich cathode couple is established and the internal micro characteristics within electrodes are investigated. A competitive relationship in the direction between particle radial and electrode thickness is observed, and therefore electrodes composed of more large particles have a higher utilization at aluminum (Al) foil current collector. There is a big difference in the average state-of-charge (SOC) between the two particles. Fortunately, the huge difference between particles can be balanced out during the constant voltage process or rest period. According to the model, electrodes with big particles besides the separator and small particles besides the current collector may exhibit the best overall performance and an appropriate kinetic matching between cathode and anode is more beneficial to high-rate charging, rather than a superior positive electrode alone, taking the lithium plating risk into account. Graphical abstract: Image, graphical abstract